Gingival Cyst of the Adult: A Case Description with a Relevant Literature Analysis - Marta Forte; Antonio d’Amati; Alfonso Manfuso; Massimiliano Vittoli; Giorgia Girone; Eliano Cascardi; Saverio Capodiferro (Reports, 2024)
Gingival cysts of the adult are rare and benign odontogenic lesions of the oral cavity, accounting for almost 0.3% of all odontogenic cysts. Their differential diagnosis is still challenging for surgeons as it includes other gingival inflammatory or non-inflammatory lesions and peripheral odontogenic tumors. The aim of this paper is to report a new case occurring in an adult, analyzing the clinical, radiographic, and histopathological features as guidelines for a differential diagnosis. We report a 49-year-old patient complaining of a small, pigmented lesion localized on the attached gingiva with no history of trauma, which was surgically excised and histologically diagnosed as a gingival cyst. A differential diagnosis may be challenging for clinicians it includes a wide spectrum of inflammatory and non-inflammatory lesions, so a correct diagnostical–therapeutical approach is needed to avoid possible overtreatment and minimize the recurrence rate.